1997
DOI: 10.1073/pnas.94.25.13499
|View full text |Cite
|
Sign up to set email alerts
|

Ultraspiracle: An invertebrate nuclear receptor for juvenile hormones

Abstract: Juvenile hormones (JH), a sesquiterpenoid group of ligands that regulate developmental transitions in insects, bind to the nuclear receptor ultraspiracle (USP). In f luorescence-based binding assays, USP protein binds JH III and JH III acid with specificity, adopting for each ligand a different final conformational state. JH III treatment of Saccharomyces cerevisiae expressing a LexA-USP fusion protein stabilizes an oligomeric association containing this protein, as detected by formation of a protein-DNA compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
149
0
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(155 citation statements)
references
References 42 publications
1
149
0
5
Order By: Relevance
“…These data suggest that the USP homodimer alone is not sufficient to cause JH induced reporter activity shown in insect cells (Jones and Sharp, 1997). Other cofactors present in insect cells may be necessary for USP homodimerization and transactivation of the reporter gene placed under the control of DR12 element.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These data suggest that the USP homodimer alone is not sufficient to cause JH induced reporter activity shown in insect cells (Jones and Sharp, 1997). Other cofactors present in insect cells may be necessary for USP homodimerization and transactivation of the reporter gene placed under the control of DR12 element.…”
Section: Discussionmentioning
confidence: 87%
“…Many attempts have been made to identify nuclear JH receptors. Jones and Sharp (1997) showed that JH III binds to the Drosophila melanogaster USP protein (a homologue of the vertebrate retinoid X receptor RXR), promoting its homodimerization, but the JH concentrations required for binding are several orders of magnitude higher than its physiological titre (Bownes and Rembold, 1987). Subsequent studies showed that USP from D.melanogaster can bind to the DR12 response element.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the JH esterase gene studied here is very tightly regulated temporally, because its induction in response to JH [20,45] at precisely the right time during the dramatic changes of metamorphosis is crucial for development, and its temporal misexpression is disastrous [46,47]. JH, an invertebrate structural relative of retinoic acid, binds to a nuclear receptor, ultraspiracle [48], that is a member of the nuclear hormone receptor family. Some nuclear hormone receptors activate transcription by acting through proteins binding to the initiator element [49], whereas in other genes the receptor may repress transcription by binding directly across the initiator element [50].…”
Section: Discussionmentioning
confidence: 99%
“…Research in the mode of action of JH is hampered by the lack of knowledge on, either nuclear or intracellular, JH receptors (see Davey, 2000). However, the discovery that JH binds to the nuclear receptor USP (Jones and Sharp, 1997), the heterodimer partner of the ecdysone receptor (Yao et al, 1993), and the subsequent finding that JH downregulates the expression of one USP isoform in Manduca sexta epidermis resulting in prevention of pupal commitment of the epidermal cells (Hiruma et al, 1999), reveal that there is a complex manner of modulation by JH of the ecdysteroid receptor complex. Thus, we propose that this JH mimic, fenoxycarb, may act by interference with the ecdysone receptor complex, as suggested for JH by Jones and Sharp (1997), resulting in accelerated switching on of the ecdysteroid-controlled developmental pathway and the subsequent induction of stage-specific ecdysteroid-regulated genes that are responsible for the pupal-adult differentiation.…”
Section: Discussionmentioning
confidence: 99%